ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI SPLDV DITINJAU DARI GAYA BELAJAR SISWA DI SMP NEGERI 2 SUNGAI KAKAP - Selvia Wilyana; Muhamad Firdaus; Iwit Prihatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze in depth the mathematical communication skills possessed by students at SMP Negeri 2 Sungai Kakap in terms of the learning styles possessed by students with three learning styles, namely visual, auditory and kinesthetic. This research is a descriptive qualitative research method in the form of a case study. In this research, the case that will be studied is how mathematical communication skills in SPLDV material are viewed from students' learning styles. Data collection tools in research are questionnaires, tests and interviews. The subjects of this research were 26 students in class VIII B of SMP Negeri 2 Sungai Kakap. In this study, it was concluded that students with a high auditory learning style had stronger mathematical communication skills, while students with a visual and auditory learning style experienced difficulties in mathematical communication indicators. It is hoped that these findings can help in formulating strategies to improve mathematical communication skills and learning style questionnaires in mathematics learning.